2019
DOI: 10.3390/molecules24081527
|View full text |Cite
|
Sign up to set email alerts
|

DP4-Assisted Structure Elucidation of Isodemethylchodatin, a New Norlichexanthone Derivative Meager in H-Atoms, from the Lichen Parmotrema tsavoense

Abstract: A phytochemical investigation of the foliose lichen Parmotrema tsavoense (Krog and Swinscow) Krog and Swinscow (Parmeliaceae) resulted in the isolation of a new trichlorinated xanthone, isodemethylchodatin. The structure elucidation of this new norlichexanthone derivative proved tricky owing to proton deficiency, and to the lack of NMR data of closely related analogues. The structure of this compound was determined based on an integrated interpretation of 13C-NMR chemical shifts, MS spectra, and DP4-based comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The minute amounts of the newly reported diphenylethers 4-6 prevented the acquisition of a 13 C NMR spectrum of satisfactory quality so that structure elucidation relied on inverse-detection heteronuclear NMR spectra. Nevertheless, these structures are meager in H atoms, with Crews scores below 1, and therefore exhibit silent fragments [35], a common situation in lichen specialized metabolites that are often highly substituted, aromatic structures [36]. Fortunately, the missing signals affected constant parts of all the compounds described in this publication (C-1′, C-5′, and C-6′) and did not cast any doubt regarding the soundness of the proposed structure elucidations.…”
Section: Resultsmentioning
confidence: 69%
“…The minute amounts of the newly reported diphenylethers 4-6 prevented the acquisition of a 13 C NMR spectrum of satisfactory quality so that structure elucidation relied on inverse-detection heteronuclear NMR spectra. Nevertheless, these structures are meager in H atoms, with Crews scores below 1, and therefore exhibit silent fragments [35], a common situation in lichen specialized metabolites that are often highly substituted, aromatic structures [36]. Fortunately, the missing signals affected constant parts of all the compounds described in this publication (C-1′, C-5′, and C-6′) and did not cast any doubt regarding the soundness of the proposed structure elucidations.…”
Section: Resultsmentioning
confidence: 69%
“…Several studies have reported that lichen metabolites possess potent α-glucosidase inhibitory activity [3][4][5]. In previous studies on the Vietnamese lichen Parmotrema tsavoense, we described several novel depsidones and diphenyl ethers [6][7][8]. However, there has been no investigation on the presence of α-glucosidase inhibitors in this lichen.…”
Section: Introductionmentioning
confidence: 94%
“…[2][3][4][5][6][7] Unfortunately, the first easily located publication [8] using the term Crews' rule gives the critical H/C atom ratio as 2 rather than the value of 1 given in the original paper. This error has propagated through the literature [9][10][11][12][13][14][15][16][17][18] and continues to do so to this day. [19][20][21] This is rather surprising as Crews' rule is normally cited in the context of solving the structures of protondeficient molecules.…”
mentioning
confidence: 99%